Pertumbuhan Janin Terhambat Sebagai Faktor Risiko Penyakit Kardiovaskular - Herlina Dimiati (Jurnal Kardiologi Indonesia, 2012)
Cardiovascular disease kills more people and disabilities in developing countries than any other disease. During few decades CVD is presumed as a generative disease which is influenced of geneticfactor, life style, smoking, exercise and obesity. Recent studies by Barkeret allhave demonstrated a consistent relationship between Cardiovascular mortality and birthweight. Intra uterine growth restriction (IUGR) is arisk factor CVD in adults.